Uji Efektivitas Biopestisida Nabati dari Gulma Rumput Teki dan Daun Kirinyuh dalam Mengendalikan Hama Wereng Pada Tanaman Padi - Pasya, Kamal; Trienita, Giesty; Widayoko, Agus (Jurnal Integrasi Sains dan Quran, 2025)
The purpose of this research is to utilize weed grass and kirinyuh leaves as raw materials for making biopesticides and test their effectiveness in controlling leafhopper pests in rice plants. In addition, it is also an innovation in making natural pesticides to reduce the use of chemical pesticides in Indonesia. The research method used is descriptive with a quantitative approach. The type of research used is a comparative method which compares one or more variables in two or more different samples, or at different times. The focus of this description is the effectiveness of biopesticides from teki grass weeds and kirinyuh leaves. Data collection was carried out by experiments and literature studies. Experiments were conducted to determine the effectiveness of the product and literature studies were conducted to analyze the effectiveness of biopesticides from weed grass and kirinyuh leaves. The indicator of product effectiveness is that leafhopper pests shrivel and change color. Based on the test results, it was found that biopesticides from weed grass and kirinyuh leaves had a pest mortality value of 88.24%, efficacy of 87.88%, inhibition and development of pests of 88%, and had a pH level of 6. Suggestions for further research are to use other plant materials that are even more effective in controlling leafhoppers with minimum toxic effects.